Phylogenetic revision of the South American notopithecines (Mammalia: Notoungulata) - Vera, Bárbara Soledad (2016)
A phylogenetic analysis of all Eocene taxa assigned to Notopithecinae has been conducted, evaluating relationships amongst notopithecines, basal interatheriids and Interatheriinae. Other groups of native ungulates were also included. New dental and postcranial characters are considered with respect to previously published data; some characters are evaluated in notoungulates for the first time. Two different searches were performed under parsimony and equal weights. The inclusion of postcranial characters strongly influenced tree topology. The most significant result of the phylogenetic analysis was the identification of a novel monophyletic group, including species traditionally grouped as Patagonian Notopithecinae. The ‘notopithecid’ name is linked to the new clade defined as the clade stemming from the most recent common ancestor of the species Notopithecus adapinus, Antepithecus brachystephanus, Transpithecus obtentus and Guilielmoscottia plicifera. This phylogeny supports the main morphological differences of the new clade with respect to Interatheriinae Interatheriidae. In consequence, a diagnosis is proposed based on phylogenetic results, to which some other morphological characters are added. The Chilean basal interatheriids Johnbell and Ignigena as well as Punapithecus (Argentinean Puna) are excluded from the notopithecid clade, implying biostratigraphical and biogeographical changes. Notopithecid distribution now becomes restricted to the middle–late Eocene part of the Sarmiento Formation outcropping in central Chubut and north-east Santa Cruz provinces, Argentina. Other extra-Patagonian records of notopithecids are not confirmed. The resulting phylogeny resolves some relationships within basal interatheriids differently from previous analyses. Interatheriinae is not recovered as a monophyletic group, and Oldfieldthomasiidae and Henricosborniid are paraphyletic. The position of the Archaeopithecidae Acropithecus rigidus is controversial; it appears at the base of the Typotheria lineage or in the notopithecid clade, but systematic taxonomy and phylogenetic relationships amongst members of Archaeopithecidae remain to be established.